OHP-028 Cost-effectiveness of triple therapy for hepatitis C compared with dual therapy in clinical practice. (24th March 2015) - Neus, P; Cano, SM; Schoenenberger, JA; Aragones, A; Gilabert, M; Martinez, M; Martinez, B; Mangues, I
Abstract : Background: New treatments for Hep C are more effective but also increase the cost of treatment and side effects also increase. Purpose: To compare the cost effectiveness of double therapy with interferon plus ribavirin (group 1) with triple therapy including telaprevir or boceprevir (group 2). Material and methods: Cross sectional and retrospective study that included patients who started treatment for Hep C since 2014, with genotype 1 and >3 months on treatment. Computerised medical records were reviewed and the outcome of treatment defined as sustained viral response (SVR) or failure; the occurrence of anaemia and neutropenia was recorded. Prescriptions for colony stimulating factors (CSFs) was obtained from the pharmacy program. Results: 70 patients initiated treatment during the study period: 33/70 (47%) in group 2 (20 used telaprevir). Median duration of treatment in patients who ended treatment (65) was 47 weeks (IQ: 40–47). In 43 patients (66%) a sustained viral response (SVR) was achieved. Group 2 patients responded more than those in group 1: 23/28 (82%) vs. 20/37 (54%) with a relative risk of 1.52 (CI95%: 1.08–2.14). The absolute risk reduction (ARR) of no response was 28% (CI95%: 7–50%) and the number needed to treat (NNT) was 3.56 (CI95%: 2.02–15.01). Mean global cost for group 1, including hematopoietic stimulating factors, was €16, 769 ± 5, 063 while for group 2 it was 39, 849 ± 9, 640. These results yielded an incremental cost-effectiveness ratio (ICER) of 82, 164 euros (CI95%:46, 621–34, 430). Haematological toxicity that needed CFSs affected 30/70 patients (43%). This finding was higher in group 2 than in group 1, without statistical significance: 16/28 (57.1%) vs. 14/37 (37%) respectively. Treatment of haematological toxicity added a mean of €2, 490 ± 2, 494 per course. Conclusion: Treatment with triple therapy is more effective than dual but it's ICER is very high from the payer's perspective. Given the large socioeconomic impact of Hep C, an approach based on cost-utility analysis would be preferable from a societal perspective. Reference: Wendt A, Bourlire M. An update on the treatment of genotype 1 chronic hepatitis C infection: lessons from recent clinical trials. Ther Adv Infect Dis 2013;1(6):191–208 No conflict of interest.